Biophysical probing of Spartina maritima photo-system II changes during prolonged tidal submersion periods - Duarte, B. (2014)
Submergence is one of the major constrains affecting wetland plants, with inevitable impacts on their physiology and productivity. Global warming as a driving force of sea level rise, tend to increase the submersion periods duration. Photosynthesis biophysical probing arise as an important tool to understand the energetics underlying plant feedback to these constrains. As in previous studies with Spartina maritima, there was no inhibition of photosynthetic activity in submerged individuals. Comparing both donor and acceptor sides of the PSII, the first was more severely affected during submersion, driven by the inactivation of the OEC with consequent impairment of the ETC. Although this apparent damage in the PSII donor side, the electron transport per active reaction centre was not substantially affected, indicating that this reduction in the electron flow is accompanied by a proportional increase in the number of active reaction centres. These conditions lead to the accumulation of excessive reducing power, source of damaging ROS, counteracted by efficient energy dissipation processes and anti-oxidant enzymatic defences. This way, S. maritima appears as a well-adapted species with an evident photochemical plasticity towards submersion, allowing it to maintain its photosynthetic activity even during prolonged submersion periods.